Hypnotherapy Improve Motivation And Learning Outcomes Students In The Block System Learning Method - Agis Taufik; Arif Setyo Upoyo (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2019)
Introduction: Block system learning requires students to learn independently and achieve predetermined achievements. Students are required to be able to adapt quickly to this situation, so as to cause various mental and emotional changes, the problem is not all students are ready to accept change. More rigorous changes and academic competition will have an impact on decreasing learning motivation which affects student learning outcomes. Hypnotherapy is a psychological therapy that uses hypnosis methods with certain techniques to deal with psychological problems. Objective: This study was conducted to determine the effect of hypnotherapy on learning motivation and student achievement index.Method: Experimental research design with pre and post approach group with control group design. Sampling used purposive sampling, the number of samples was 70. The intervention group received therapy once a week for 4 weeks. The motivation was measured before and after treatment with a questionnaire.Result: The average score of the learning motivation is 6.8 and the average value of the achievement index difference is 0.099 with a P value of 0.001. Discussion: The results of this test provide an overview in the intervention group, that there is a significant increase in the value of learning motivation and achievement index in students.Conclusion: Hypnotherapy can be used as reference material to become an alternative therapy to overcome students' psychological problems.